Population Ageing Exemplified by RF and Mongolia in the Looking Glass of a Cross-country Analysis – Regional Aspect - Omakaeva, Ellara U. (International Journal of Psychosocial Rehabilitation, 2020)
Population ageing is considered in this study as a part of the global demographic problem by comparative analysis of the state of the elderly people in Russia and Mongolia. A research of scientific literature on this matter reveals, that the problem has not been studied as such. The problem under study is due to the scale of the demographic ageing making the nature and regularities of this phenomenon even more topical. Is it the same for all countries or specific to some of them and particular regions? This article is aimed to comprehensively comparatively analyse the world’s demographic situation in order to reveal a correlation and differences between the two neighbouring countries as well as to find exploratory tools for sociological surveys under the scientific project entitled “Elderly Person in the Economic Space of the Modern Dynamic Societies of Russia and Mongolia: a Cross-country Analysis”. The choice of the exploration partners was determined by the following: besides the intrinsically global nature of the problem itself (implying a wide international cooperation by default), the results of joint scientific research may be of a practical interest for neighbouring countries with similar social, religious and historic backgrounds. The research is an interdisciplinary one implying understanding and reflection from the points of view of sociology, economy, philosophy, linguistics, cultural science and law. The article may be useful to the researchers of this matter (sociologists, psychologists etc.), public officials and social professionals developing regional and federal programmes to protect and support elderly people.